2011
DOI: 10.1186/1471-2261-11-59
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peripheral arterial disease in subjects with moderate cardiovascular risk: Italian results from the PANDORA study Data from PANDORA (Prevalence of peripheral Arterial disease in subjects with moderate CVD risk, with No overt vascular Diseases nor Diabetes mellitus)

Abstract: BackgroundThe PANDORA study has recently examined the prevalence of low ankle brachial index (ABI) in subjects with moderate risk of cardiovascular disease. This sub-analysis of the PANDORA study examines the prevalence of asymptomatic peripheral arterial disease (PAD), as determined by ABI, in Italian subjects presenting with moderate cardiovascular risk, in the absence of diabetes or overt vascular disease.MethodsPANDORA is a non-interventional, cross-sectional study that was performed in 6 European countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…Eight studies (14.5%) recruited only men,32 39 51 56 58 60 71 72 2 (3.6%) only women,53 54 and 45 (81.8%) both 21–31 33–38 40–50 52 55 57 59 61–70 73–75. Forty-three (78.2%) were cross-sectional studies,22–26 28–31 33 34 36 40–45 47–50 52–55 57–71 74 75 10 (18.2%) were cohort studies21 27 32 38 39 46 51 56 72 73 and 2 (3.6%) were case-control studies 35 37. Forty-seven (84.5%) studies defined PAD using the ABI,21–26 29–34 36–38 40–49 52–55 57–71 73–75 and 7 (12.7%) based on symptoms of intermittent claudication, using either the Edinburgh, WHO/Rose or San Diego claudication questionnaires 28 35 39 50 51 56 72.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (14.5%) recruited only men,32 39 51 56 58 60 71 72 2 (3.6%) only women,53 54 and 45 (81.8%) both 21–31 33–38 40–50 52 55 57 59 61–70 73–75. Forty-three (78.2%) were cross-sectional studies,22–26 28–31 33 34 36 40–45 47–50 52–55 57–71 74 75 10 (18.2%) were cohort studies21 27 32 38 39 46 51 56 72 73 and 2 (3.6%) were case-control studies 35 37. Forty-seven (84.5%) studies defined PAD using the ABI,21–26 29–34 36–38 40–49 52–55 57–71 73–75 and 7 (12.7%) based on symptoms of intermittent claudication, using either the Edinburgh, WHO/Rose or San Diego claudication questionnaires 28 35 39 50 51 56 72.…”
Section: Resultsmentioning
confidence: 99%
“…10 If the slope of the flame was unclear, baseline shifting was used to change the aliasing velocity until a clear delineation of isovelocity slope was seen. 10 If the slope of the flame was unclear, baseline shifting was used to change the aliasing velocity until a clear delineation of isovelocity slope was seen.…”
Section: Ankle-brachial Blood Pressure Index (Abi) Measurementsmentioning
confidence: 99%
“…To determine the ABI, systolic blood pressures of the brachial, anterior, and posterior tibial arteries were measured using a mercury manometer with inflatable cuffs. 10,11 A handheld vascular arterial Doppler was used to accurately hear the Korotkoff sounds on the anterior tibial artery. The maximum ankle arterial pressures were divided by the maximum of the brachial arterial pressures to calculate the ABI.…”
Section: Ankle-brachial Blood Pressure Index (Abi) Measurementsmentioning
confidence: 99%
“…Firstly, due to their indepth knowledge of their patients, they are able to appropriately select at risk patients for screening, which should include those listed in table 4 below. Evidence from the recent eurpoean PANDORA study looking at the prevalence of asymptomatic PAD using ABI<0.9, found that many PAD diagnosed patients failed to meet the screening requirements for ABI testing, which may lead to a broadening of the screening criteria to include more patients (Sanna et al, 2011).…”
Section: Wwwintechopencommentioning
confidence: 99%